Исаак Ньютон, 1643-1727 - Вавилов Сергей Иванович (Научно-биографическая серия, 1989)
Экземпляры: КХ (20110414) / Инвентарный номер: 936375 / Цена: 1.20 / Сис.шифр: 22.3 / Авт.знак: В 12 / ГРНТИ: 27 / ББК: 22.3д